(untitled) (Medical Forum Monthly, 2024)
Objectives: To find out the seroprevalence of HIV detected on blood screening in population of Southern Punjab. Study Design: Observational Study Place and Duration of Study: This study was carried out at the Department of Pathology, Combined Military Hospital (CMH), Multan from January to December 2013. Materials and Methods: Serological blood screening of blood donors and candidates coming for recruitment in armed forces of Pakistan at CMH Multan Center was performed. Suspected cases confirmed with third generation ELISA technique. Bio-data of HIV positive cases was collected, analyzed and compared with national and international literature. Results: A total of 10666 persons were screened out. Only two (0.018%) was HIV positive. Conclusion: Seroprevalence of HIV/ AIDS is less common in our country as compared to rest of the world especially than that of neighbor countries. Awareness of the disease along with prophylactic and preventive measures are necessary to decrease the prevalence and spread of this disease.